This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: Problem 2, Chapter 2 from Shuler and Kargi - Solution by Krishnan Chittur (email@example.com) I have added some comments to help you understand the Maple Calculations restart is like starting Maple all over again - so any assignments you may have made are wiped out > restart; Start writing down the equations first and then solve them. Notice that Maple differentiates between := and = (one has a colon before the equal to and is the assignment statement (which is different from the equal to sign)) After you set up the equations, we solve them - > eq1:= k*E(t)*S(t)+k[-2]*E(t)*P(t)-k[-1]*ES(t)-k*ES(t)=0; := eq1 = +-- k 1 ( ) E t ( ) S t k-2 ( ) E t ( ) P t k-1 ( ) ES t k 2 ( ) ES t > eq2:=rate=k*ES(t)-k[-2]*E(t)*P(t); := eq2 = rate- k 2 ( ) ES t k-2 ( ) E t ( ) P t > eq3:=ES(t)=E-E(t); := eq3 = ( ) ES t- E ( ) E t Now solve for E(t) from equation 1 - We use the function called solve from Maple - what we are doing here is to solve equation 1 for E(t) - In maple, you can solve an equation for any of the variables you like -...
View Full Document
- Fall '09